The development of the male second antenna in Polyartemiella hazeni (Murdoch, 1884) with a morphological definition of the Chirocephalidae (Crustacea: Anostraca) - Rogers, D. Christopher (Zootaxa, 2003)
The second antenna of male anostracans in the genera Polyartemia and Polyartemiella are described as polyramous, unsegmented structures. This is in sharp contrast to males of all other anostracan genera, which bear variously ornamented, uniramal second antenna that are secondarily two-segmented. By following the development of the second antenna of male P. hazeni through various instars, I found that the posterior ramus is the actual second antenna, unsegmented, and that the remaining rami represent a rigid antennal appendage, a structure common to the majority of genera within the Chirocephalidae. In addition, the family Chirocephalidae is redefined, the genus Galaziella is synonymized with Chirocephalus, and a key to genera and a checklist of described species is provided.